The role of psychological characteristics in facilitating the pathway to elite performance part 2: Examining environmental and stage-related differences in skills and behaviors - MacNamara, A.; Button, A.; Collins, D. (The Sport Psychologist, 2010)
MacNamara, Button, & Collins (under review) proposed that if individuals are to fulfill their potential they must possess and systematically develop a specific set of skills (termed Psychological Characteristics of Developing Excellence or PCDEs) that allow them to interact effectively with the developmental opportunities they are afforded. Given the complexity of the developmental pathway, it may well be that different skills are needed at different stages of development and across different performance domains. Twenty-four elite participants from team sports, individual sports, and music were purposefully sampled from different domains and interviewed on their experiences of their own pathways to excellence. Results suggested that although PCDEs were important throughout development, the manner by which they were deployed depended on stage, domain, and the characteristics of the individual performer. These findings support proposals to systematically incorporate PCDEs into TID practices because these may be the key feature in maintaining progress toward excellence.